2005
DOI: 10.1128/aem.71.8.4945-4949.2005
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of a Bacteroides thetaiotaomicron Marker for Human Feces

Abstract: A bacterial primer set, known to produce a 542-bp amplicon specific for Bacteroides thetaiotaomicron, generated this product in PCR with 1 ng of extracted DNA from 92% of 25 human fecal samples, 100% of 20 sewage samples, and 16% of 31 dog fecal samples. The marker was not detected in 1 ng of fecal DNA from 61 cows, 35 horses, 44 pigs, 24 chickens, 29 turkeys, and 17 geese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 27 publications
2
62
0
Order By: Relevance
“…Several studies have reported 100% host specificity of the HF183 marker for non-human fecal samples [51,[66][67][68][69][70]. In contrast, the occasional presence of the HF183 markers in non-human fecal samples has also been reported [52,57,61,71,72], particularly in dog, deer, and chicken feces.…”
Section: Host Specificitymentioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have reported 100% host specificity of the HF183 marker for non-human fecal samples [51,[66][67][68][69][70]. In contrast, the occasional presence of the HF183 markers in non-human fecal samples has also been reported [52,57,61,71,72], particularly in dog, deer, and chicken feces.…”
Section: Host Specificitymentioning
confidence: 92%
“…Therefore, cross-reactivity may occur when this region is targeted for MST marker development [56]. It has been suggested that genes directly involved in host-microbe interactions may provide more host specificity than the highly conserved 16S rRNA gene, and may, therefore, be suitable targets for marker development [57]. Several researchers developed qPCR assays targeting Bacteroides genes other than those for 16S rRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MST methods that do not require cultivation, such as the direct detection of bacterial 16S rRNA gene sequences using PCR, are becoming more widespread (5,9). While these assays have now been used in field applications (5,9,20), a recent study demonstrates understandable cross-reactivity when highly conserved genomic regions are targeted (7). Since ribosomal genes are not directly involved in microbe-host interactions, it is possible that other bacterial genetic markers encoding factors related to host specificity might be better candidates for MST assays.…”
mentioning
confidence: 99%
“…Both ruminant and human-associated Bacteroidales markers (RBac and HBac) tested positive for their target host organisms, however, they also displayed cross-reactivity with brush-tail possums (as confirmed from sequencing for HBac), other marsupials, gulls and rabbits. Bacteroidales markers have been widely used overseas and have shown limited crossreactivity with other organisms*HBac markers have been detected from dog (Carson et al 2005;Kildare et al 2007;Harwood et al 2009), cat (Kildare et al 2007) and chicken faeces (Carson et al 2005;Kildare et al 2007;Gourmelon et al 2007;Harwood et al 2009), and the RBac marker has detected in faeces from chickens (Ahmed et al 2008a), horse (this study and V. Harwood, personal communication), pigs (Gourmelon et al 2007) and humans (Gourmelon et al 2007). Overall, the sensitivity (100% for faecal and wastewater samples both) and specificity (87%) of the HBac marker assay was comparable with the sensitivity and specificity reported in the studies conducted in the USA (sensitivity 50Á85% and 100% for faecal and wastewater samples, and specificity 86Á100%; Bernhard & Field 2000b;Carson et al 2005), in France (sensitivity 86Á98% and specificity 94Á99%; Gourmelon et al 2007) and in Australia (sensitivity 100% and specificity 100%; Ahmed et al 2008a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroidales markers have been widely used overseas and have shown limited crossreactivity with other organisms*HBac markers have been detected from dog (Carson et al 2005;Kildare et al 2007;Harwood et al 2009), cat (Kildare et al 2007) and chicken faeces (Carson et al 2005;Kildare et al 2007;Gourmelon et al 2007;Harwood et al 2009), and the RBac marker has detected in faeces from chickens (Ahmed et al 2008a), horse (this study and V. Harwood, personal communication), pigs (Gourmelon et al 2007) and humans (Gourmelon et al 2007). Overall, the sensitivity (100% for faecal and wastewater samples both) and specificity (87%) of the HBac marker assay was comparable with the sensitivity and specificity reported in the studies conducted in the USA (sensitivity 50Á85% and 100% for faecal and wastewater samples, and specificity 86Á100%; Bernhard & Field 2000b;Carson et al 2005), in France (sensitivity 86Á98% and specificity 94Á99%; Gourmelon et al 2007) and in Australia (sensitivity 100% and specificity 100%; Ahmed et al 2008a, b). In contrast, the sensitivity of the RBac marker was 85% and specificity 65%, which is considerably lower when compared with the studies conducted in the USA (97Á100% sensitivity, 100% specificity; Bernhard & Field 2000b) and in Australia (sensitivity 100% and specificity 97%; Ahmed et al 2008a), but similar to the results reported for samples collected in France (sensitivity 100% and specificity roughly 67Á77%; Gourmelon et al 2007).…”
Section: Discussionmentioning
confidence: 99%